2011
DOI: 10.1093/carcin/bgr207
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3σ and p63 play opposing roles in epidermal tumorigenesis

Abstract: 14-3-3σ plays a regulatory role in epidermal epithelial differentiation and loss of 14-3-3σ leads to increased proliferation and impaired differentiation. A tumor suppressor function for 14-3-3σ has been proposed based on the fact that some epithelial-derived tumors lose 14-3-3σ expression. p63, a p53 family member, is a master regulator of epidermal epithelial proliferation and differentiation and is necessary for the epidermal development. The function of p63 in tumorigenesis is still controversial and poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Sfn has also been shown to inhibit p63 in keratinocytes (Li et al, 2011). We then tested whether Sfn and shd might cooperate to regulate p63.…”
Section: Resultsmentioning
confidence: 99%
“…Sfn has also been shown to inhibit p63 in keratinocytes (Li et al, 2011). We then tested whether Sfn and shd might cooperate to regulate p63.…”
Section: Resultsmentioning
confidence: 99%
“…14-3-3 σ , a protein associated with keratinocyte differentiation, is a direct target for ΔNp63 α repression in undifferentiated human epidermal keratinocytes [52]. Treatment of Er/+ mice on a p63 ( +/+ ) background with a two-stage carcinogenesis protocol resulted in the formation of tumors in which ΔNp63 α was strongly expressed, while loss of function of an endogenous allele of p63 in this context, which generated ( Er/+/p63 +/−) mice, resulted in reduced sensitivity to this protocol, suggestive of cooperation of ΔNp63 α in Ras/14-3-3 σ -induced tumorigenesis [125]. …”
Section: P63 and Neoplasiamentioning
confidence: 99%
“…This suggested that the epidermal hyper-proliferation observed in 14-3-3σ +/ER mice is caused by the expression of the truncated 14-3-3σ protein, which acquired additional functions and presumably an altered ligand specificity, and not by the mere loss of 14-3-3σ function. Notably, p63 and YAP1 have been shown to functionally interact with the ER mutant of 14-3-3σ in murine epidermis [28, 30]. However, we could not detect an effect of 14-3-3σ loss on the localization and expression level of p63 (Supplemental Figure 2B).…”
Section: Resultsmentioning
confidence: 66%
“…In addition, heterozygous ER -mice show an extensive hyper-proliferation of the epidermis followed by the development of multiple papillomas and squamous cell carcinoma at the age of 6 month [27]. ER -mice display increased levels of p63 in the epidermal suprabasal layers, suggesting that truncated 14-3-3σ fails to block the transcription of TP63 which may contribute to hyper-proliferation of the epidermis [28]. In addition, Yap1, an essential factor of the Hippo pathway controlling organ size and tissue homeostasis [29], is expressed in the epidermal suprabasal layers of ER -mice [30].…”
Section: Introductionmentioning
confidence: 99%